Developing a Consumer Complaining and Recovery Effort Scale - Lu, L.; Gursoy, Dogan; Chi, C.; Xiao, G. (Sage Publications Inc, 2015)
The main purpose of this study is to identify the underlying dimensions of consumer complaining and recovery effort and to develop a multidimensional scale to measure this construct. Literature suggests that the consumer complaining and recovery effort is a four-dimensional construct consisting of procedural, cognitive, time-related, and affective components. Using data collected from hotel guests, a measurement scale is developed to assess this four-dimensional construct. First, a factor analysis is conducted on one set of data. Afterward, the underlying dimensions identified by the exploratory factor analysis are confirmed by conducting a confirmatory factor analysis on a separate set of data. Findings suggest that the scale developed in this study presents substantial convergent validity, discriminant validity, predictive validity, and reliability.